Pengaruh Shopping Enjoyment dan Sales Promotion terhadap Impulsive Buying Marketplace Shopee pada Mahasiswa Universitas Riau - Meyzi Heriyanto; Devi Juniarty (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The purpose of this study was to determine the effect of shopping enjoyment and sales promotion on impulsive buying of shopee marketplace on students of Riau University. The method used is a quantitative method with a data collection technique in the form of a questionnaire responded to by 384 respondents. The sampling technique uses a purposive sampling technique. This study uses analysis such as validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression, t-test, F-test, and coefficient of determination (). Based on the analysis that has been done, the results show that shopping enjoyment and sales promotion have a positive and significant effect on impulsive buying of the Shopee marketplace for students at the University of Riau